AB0925 Gender difference in fibromyalgia: comparison between male and female patients from an italian monocentric cohort. (15th June 2017) - Guzzo, MP; Iannuccelli, C; Gerardi, MC; Lucchino, B; Valesini, G; Franco, M Di
Abstract : Background: Fibromyalgia (FM) is one of the main causes of chronic widespread pain (CWP). It is characterized by CWP, which is the cardinal symptom, and the presence of more than 11 tender points (hyperalgesia). [1] Other symptoms such as fatigue, sleep disturbances, difficulties with memory and concentration, irritable bowel syndrome, headache, depression are frequent. Worldwide mean prevalence of FM is 2, 7% with female/male ratio of 4:1. In Italy the prevalence is 3, 7% with the same female/male ratio. [2] Objectives: The aim of the study is to analyze clinical features of a cohort of male patients with CWP and to evaluate gender differences in patients diagnosed as FM. Methods: The study population consisted of 101 consecutive male subjects referred to the Clinic for the Diagnosis and Therapy of Fibromyalgia, in the period between January 2007 and October 2016, matched with a control group of 101 females with CWP referred to the clinic in the same period. Complete clinical evaluation was performed in all patients. Results: Ninety-seven male subjects (96%) were referred to the clinic for a history of musculoskeletal pain, among these 53% reported fatigue and 60% complained about sleep disorders. A stressful trigger (work or family problems, bereavement, infections) at the onset of pain was reported by 42% of patients. Fifty-two percent of patients reported mood changes. Physical examination showed hyperalgesia in 15% of the subjects and a mean tender points' (TP) count was 4.6 (range 0–18). The diagnosis of FM was performed according to ACR 1990 criteria, since the enrollment included patients referred to the clinic before the publication of the latest ACR criteria [3, 4]. Only 18 male subjects (18%) fulfilled the classifying criteria. In the female group CWP was reported by 97%, fatigue by 65%, and sleep disorders by 72% of patients. Stressful events were reported by the 50% of female population. Mood changes were described by 54% of female subjects and were predominantly depressive. Physical examination revealed hyperalgesia in 48 subjects (47%) and the mean TP count was 11 (range 0–18). The diagnosis of FM was confirmed in 60% of subjects. Comparing the two cohorts of patients with FM, mean age at the time of the visit and mean age of onset of symptoms resulted significantly higher in females than in males (p=0.02 and p=0.04 respectively). There was no statistically significant difference in the number of TP, in fatigue, sleep and mood disorders and in the percentage of stressors considered as a trigger for the disease. Hyperalgesia was the only feature more common in females than in males (p=0.03). Conclusions: The significant higher frequency of hyperalgesia in women suggests a different presentation of CPW, that is the cornerstone of FM, in the two sexes. Moreover, the prevalence of FM was higher in females than in males when 1990 ACR criteria were used. It can be assumed that further gender differences could be showed applying 2010 ACR criteria. References: Wolfe et al, 1990. Queiroz LP, 2013. Wolfe et al, 2010. Wolfe et al, 2011. Disclosure of Interest: None declared